2022
DOI: 10.3389/fnut.2022.950062
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-containing polysaccharide from Spirulina platensis alleviates Cd-induced toxicity in mice by inhibiting liver inflammation mediated by gut microbiota

Abstract: Selenium-containing polysaccharide from Spirulina platensis (Se-SPP) has been demonstrated to help in inhibiting cadmium-induced injury in mice, but the underlying mechanism has not been determined. This study aimed to investigate the beneficial effects of Se-SPP on alleviating Cd-induced toxicity in mice by targeting liver inflammatory and gut microbiota. Se-SPP supplementation for 28 days in Cd-induced toxic mice significantly mitigated liver pathological damage and inflammation, which was correlated to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Zhou et al . (2022) found that A. platensis selenium polysaccharide could significantly recover the intestinal barrier damage caused by cadmium and improve the related disease symptoms induced by Cadmium. The broad application prospects of A. platensis polysaccharides call for further research on their molecular fine chemical structure, structure–activity relationship and pharmacology.…”
Section: Functional Ingredients In Arthrospira Platensismentioning
confidence: 99%
“…Zhou et al . (2022) found that A. platensis selenium polysaccharide could significantly recover the intestinal barrier damage caused by cadmium and improve the related disease symptoms induced by Cadmium. The broad application prospects of A. platensis polysaccharides call for further research on their molecular fine chemical structure, structure–activity relationship and pharmacology.…”
Section: Functional Ingredients In Arthrospira Platensismentioning
confidence: 99%